Utilization of molecular and conventional methods for the identification of nontuberculous mycobacteria isolated from different water sources - Tortone, Claudia Andrea (2018)
Background: The environment is the nontuberculous mycobacteria (NTM) reservoir, opportunistic pathogens of great diversity and ubiquity, which is observed in the constant description of new species capable of causing infection. Since its introduction, molecular methods are essential for species identification. Most comparative studies between molecular and conventional methods, have used isolated strains from clinical samples. Methods: The aim of this study was to evaluate the usefulness of molecular methods, especially the hsp65-PRA (PCR-Restriction Enzyme Analysis), and biochemical tests in the identification of NTM recovered from water of different origins, using the sequencing of 16S rRNA and hsp 65 genes as assessment methods of the previous ones. Species identification was performed for all 56 NTM isolates what were recovered from 32 (42.1%) positive water samples, using conventional phenotypic methods, hsp65-PRA, partial sequencing of 16S rRNA and sequencing of hsp 65 genes. Results: Phenotypic evaluation and hsp65-PRA were concordant with 23 (41.1%) isolates. Also, the PRA was concordant with 16 (28.6%) and 27 (48.2%) isolates, with the partial sequencing of 16S rRNA and sequencing of hsp 65 genes, respectively. It is considered that the 19.6% (n = 11) could not be identified. Conclusion: Identification of NTM environmental isolates to the species level, especially when they are pigmented and fast-growing, both the analysis of the restriction patterns obtained by PRA and the sequencing of the 16S rRNA and hsp 65 genes are insufficient by themselves. Although they are demanding and time-consuming, biochemical tests are very useful to support data obtained by molecular methods.